1999
DOI: 10.1182/blood.v93.5.1595
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of the Thrombotic Risk in Children With Acute Lymphoblastic Leukemia Carrying the MTHFR TT 677 Genotype, the Prothrombin G20210A Variant, and Further Prothrombotic Risk Factors

Abstract: The reported incidence of thromboembolism in children with acute lymphoblastic leukemia (ALL) treated with L-asparaginase, vincristine, and prednisone varies from 2.4% to 11.5%. The present study was designed to prospectively evaluate the role of the TT677 methylenetetrahydrofolate reductase (MTHFR) genotype, the prothrombin G20210A mutation, the factor V G1691A mutation, deficiencies of protein C, protein S, antithrombin, and increased lipoprotein (a) concentrations in leukemic children treated according to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
43
1
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 172 publications
(50 citation statements)
references
References 30 publications
4
43
1
2
Order By: Relevance
“…This lesser exposure to ASP may explain the infrequent occurrence of symptomatic TE during the induction phase of treatment despite freshly inserted CVLs prior to the start of chemotherapy and the administration of steroids for 4 weeks. Symptomatic TE complicated intensification therapy in 9% of our patients; this rate is comparable with the rate of TE in children receiving concomitant ASP and steroids on contemporary ALL protocols (Nowak-Gottl et al, 1999;Kishi et al, 2003;Mathew et al, 2003).…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…This lesser exposure to ASP may explain the infrequent occurrence of symptomatic TE during the induction phase of treatment despite freshly inserted CVLs prior to the start of chemotherapy and the administration of steroids for 4 weeks. Symptomatic TE complicated intensification therapy in 9% of our patients; this rate is comparable with the rate of TE in children receiving concomitant ASP and steroids on contemporary ALL protocols (Nowak-Gottl et al, 1999;Kishi et al, 2003;Mathew et al, 2003).…”
Section: Discussionsupporting
confidence: 71%
“…The thrombogenic potential of steroids is well described in the literature (Isacson, 1970;Jorgenson et al, 1982;Zanon et al, 1982;van Giezen & Jansen, 1992;Patrassi et al, 1992;Ozturk et al, 1994;Patrassi et al, 1995;Nowak-Gottl et al, 1999, 2001aSartori et al, 1999;Athale & Chan, 2003b). Several investigators have shown that steroid therapy leads to elevation of factors VIII, von Willebrand factor (VWF), prothrombin and antithrombin, and decreases the levels of fibrinogen and plasminogen (Ozsoylu et al, 1962;Isacson, 1970;Jorgenson et al, 1982;Zanon et al, 1982;van Giezen & Jansen, 1992;Halton et al, 1992;Ozturk et al, 1994;Patrassi et al, 1995;Sartori et al, 1999).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations